Leveraging research within a pedagogical protocol for enhanced integrated-competency student learning. (September 2021) - Marshall, Thomas E.; Drum, Dawna; Morris, Steven; Lambert, Sherwood Lane
Abstract: This research presents a case-based pedagogical protocol, including an experiment, designed to maximize the utility of the integrated-competency framework in accounting. The study involves a rich learning exercise protocol requiring integrated competencies that fairly represent, in content and context, the experience of a professional engagement. The pedagogical protocol focuses on communications in the accounting industry, where research suggests potential communication disconnects. The study includes a laboratory experiment investigating how audit department communications (experimental treatment), individual attitudes, and task domain knowledge (task recall) interact to influence project participants' perspectives of project viability and their intention to continue project development. In accordance with the pedagogical protocol, we discuss experiment findings identifying significant factors influencing decision behavior with the students in a debriefing session for self-awareness and mindfulness. The debriefing session, focusing on introspection and empathy, expands the competencies generally addressed by accounting learning exercises. The experiment findings suggest the importance that the accounting profession identify the need for and complexities of effective communications across organizational units. We present the pedagogical protocol and design methodology, including leveraging social science research, as models for other educators/researchers to develop learning exercises based on the integrated-competency model to better educate and prepare our students for their future successes.